134k views
5 votes
Solve by elimination 3x+y=5 -2x-y=-10

User GPX
by
4.9k points

2 Answers

3 votes

Answer:

x = -5

y = 20

Explanation:

3x + y = 5 ⇒ y = 5 - 3x

-2x - y = -10 ⇒ 2x + y = 10

2x + (5 - 3x) = 10

5 - x = 10

x = -5

Substitution of x-value into "y = 5 - 3x":

y = 5 - 3(-5)

y = 5 + 15

y = 20

User Arif Dewi
by
4.7k points
5 votes

Answer:

(-5, 20)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination
  • Solving systems of equations by graphing

Explanation:

Step 1: Define systems

3x + y = 5

-2x - y = -10

Step 2: Solve for x

Elimination

  1. Add 2 equations together: x = -5

Step 3: Solve for y

  1. Define original equation: 3x + y = 5
  2. Substitute in x: 3(-5) + y = 5
  3. Multiply: -15 + y = 5
  4. Add 15 on both sides: y = 20

Step 4: Graph systems

Check the solution set and graph.

Solve by elimination 3x+y=5 -2x-y=-10-example-1
User Fanis Mahmalat
by
5.0k points